Cynthia Ann Parker : Indian captive - Gonzalez, Catherine Troxell (Stories for young Americans series., 1980)
Tells the story of Cynthia Ann Parker's covered wagon trip from Illinois to East Texas, the massacre at Fort Parker, her capture and life among the Comanche Indians, her marriage to Chief Peta Nocona, her family life and finally her tragic recapture and return to East Texas.